Data security using low bit encoding algorithm and rsa algorithm - Ramadhan, Yusuf; Suhardi, Suhardi; Aditama, Yuda (Jurnal Mantik, 2024)
Ensuring the security of messages and information is paramount in today's digital era. This study proposes a combined approach using the RSA algorithm for cryptography and the Low Bit Encoding (LBE) algorithm for steganography to enhance security measures. The security process involves encrypting plaintext messages into ciphertext, which are then embedded into MP3 audio files as cover objects. Evaluation is conducted by measuring the Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR) of the stego audio. Research findings indicate an MSE value of approximately 0.6 and a PSNR of 62.2 dB, indicating high-quality audio files. The integration of these algorithms offers a robust security level, ensuring effective message confidentiality. This research contributes to a deeper understanding of cryptography and steganography techniques in safeguarding sensitive information during digital communication